Single dose treatment with H2 receptor antagonists: is bedtime administration too late?. Issue 4 (April 1987) - Merki, H; Witzel, L; Harre, K; Scheurle, E; Neumann, J; Röhmel, J
Abstract : Using ambulatory ph-metry, intragastric acidity was measured over three separate 24 hour periods in each of 12 healthy volunteers receiving either (a) placebo (1800 h and 2200 h), (b) 300 mg ranitidine (1800 h) and placebo (2200 h), or (c) placebo (1800 h) and 300 mg ranitidine (2200 h). Ranitidine was significantly more effective in decreasing 24 h median intragastric acidity when the drug was administered at 1800 h rather than at 2200 h. Median pH (and interquartile range) was 1.45 (1.4-1.7) on placebo, 2.55 (2.05-3.2) on ranitidine given at 2200 h and 3.35 (2.5-3.85) on ranitidine given at 1800 h (p less than 0.004). The total duration of highly acidic electrode readings (pH less than 1.5) over a 24 h period was reduced significantly by administering the H2-receptor antagonist at 1800 h compared with the later administration. It is suggested that treatment of duodenal ulcers by single administration of ranitidine in the early evening should be evaluated by clinical trial.